2019
DOI: 10.1590/1982-0224-20190043
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and longitudinal variation in fish assemblage structure along an unregulated stretch of the Middle Uruguay River

Abstract: Diversity patterns and their causes remain important questions, especially for ecosystems that preserve natural conditions. This is the case of fish diversity in large Neotropical rivers. In this context, we investigated fish diversity patterns along an extensive unregulated river section (ca. 450 km) in the Middle Uruguay River Basin. Sampling was conducted seasonally between May 2017 and March 2018, at six sites (patches) with contrasting environmental conditions. We collected 3,008 individuals belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
1
6
0
1
Order By: Relevance
“…Juveniles probably disperse to other reaches, where recruitment is limited by river regulation, pollution and deforestation (Zaniboni‐Filho & Schulz, 2003; Reynalte‐Tataje et al, 2012; Lopes et al, 2019a). In fact, Mounic‐Silva et al (2019) recorded more juveniles in the Middle than in the Upper Uruguay, and Massaro et al (2019) reported high diversity and abundance of migratory fishes in this river segment.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Juveniles probably disperse to other reaches, where recruitment is limited by river regulation, pollution and deforestation (Zaniboni‐Filho & Schulz, 2003; Reynalte‐Tataje et al, 2012; Lopes et al, 2019a). In fact, Mounic‐Silva et al (2019) recorded more juveniles in the Middle than in the Upper Uruguay, and Massaro et al (2019) reported high diversity and abundance of migratory fishes in this river segment.…”
Section: Discussionmentioning
confidence: 97%
“…Contrasting with other main rivers of the La Plata basin (Paraguay and Paraná rivers), the Uruguay is substantially channelized with limited development of floodplains and wetlands, which are formed mainly by the confluence with some tributaries. However, studies have reported the presence of migratory fish, with evidence of regional recruitment (Zaniboni‐Filho & Schulz, 2003; Reynalte‐Tataje et al, 2012; Massaro et al, 2019), including the location of spawning sites and the drift of eggs and larvae (Côrrea et al, 2011; Ávila‐Simas, Reynalte‐Tataje & Zaniboni‐Filho, 2014; Pachla et al, 2020; Reynalte‐Tataje et al, 2020). Fish recruitment dynamics, however, remain poorly understood, in particular because the location of nursery grounds remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nesse sentido, pode-se considerar que este indivíduo seja potencialmente um dispersor. Contudo, ressalta-se que próximo ao trecho do registro o rio Uruguai possui uma largura aproximada de 1250 m (Massaro et al, 2019), podendo agir como barreira física para esta espécie. Ainda, a região do registro está inserida no bioma Pampa, caracterizado por vastas planícies, vegetação campestres, e pelo clima mesotérmico, subtropical com verões quentes sem seca definida e invernos rigorosos (Köppen, 1936;Alvares et al, 2013).…”
Section: Annexunclassified